The relationship between executive function and fine motor control in young and older adults - Corti, E.; Johnson, A.; Riddle, H.; Gasson, Natalie; Kane, R.; Loftus, A. (Elsevier BV; North Holland, 2017)
The present study examined the relationship between executive function (EF) and fine motor control in young and older healthy adults. Participants completed 3 measures of executive function; a spatial working memory (SWM) task, the Stockings of Cambridge task (planning), and the Intra-Dimensional Extra-Dimensional Set-Shift task (set-shifting). Fine motor control was assessed using 3 subtests of the Purdue Pegboard (unimanual, bimanual, sequencing). For the younger adults, there were no significant correlations between measures of EF and fine motor control. For the older adults, all EFs significantly correlated with all measures of fine motor control. Three separate regressions examined whether planning, SWM and set-shifting independently predicted unimanual, bimanual, and sequencing scores for the older adults. Planning was the primary predictor of performance on all three Purdue subtests. A multiple-groups mediation model examined whether planning predicted fine motor control scores independent of participants' age, suggesting that preservation of planning ability may support fine motor control in older adults. Planning remained a significant predictor of unimanual performance in the older age group, but not bimanual or sequencing performance. The findings are discussed in terms of compensation theory, whereby planning is a key compensatory resource for fine motor control in older adults.